The Influence Of Culinary Students Nutrition Knowledge On Fast Food Consumption - Seillamita Yesi Ramadani; Rina Rachmawati (Universitas Negeri Padang, 2026)
This study aims to determine the effect of nutritional knowledge on fast food consumption among students of the Culinary Education Study Program at Universitas Negeri Semarang. The study employed a quantitative approach using a survey method. The research population consisted of 279 students from the 2022, 2023, and 2024 cohorts, with a sample of 164 respondents selected through simple random sampling. Data were collected through questionnaires using a Likert scale. Furthermore, the data were analyzed using simple linear regression with the assistance of SPSS software.The results showed that the students’ level of nutritional knowledge was categorized as fairly good, with an average score of 78.42. Meanwhile, the level of fast food consumption was still relatively high, with an average score of 66.18. The regression analysis produced a regression coefficient of -0.186, indicating a negative relationship between nutritional knowledge and fast food consumption. However, the partial test result showed a significance value of 0.585 (>0.05), indicating that nutritional knowledge did not have a significant effect on fast food consumption among Culinary Education students at UNNES.The findings suggest that students’ consumption behavior is influenced not only by nutritional knowledge but also by other factors, such as lifestyle, practicality, price, ease of access, and social environmental influences. Therefore, improving nutritional knowledge alone is not sufficient to reduce fast food consumption among university students.